Prevalence of Flp Pili-Encoding Plasmids in Cutibacterium acnes Isolates Obtained from Prostatic Tissue - Davidsson, Sabina; Carlsson, Jessica; Mölling, Paula; Gashi, Natyra; Andrén, Ove; Andersson, Swen-Olof; Brzuszkiewicz, Elzbieta; Poehlein, Anja; Al-Zeer, Munir A.; Brinkmann, Volker; Scavenius, Carsten; Nazipi, Seven; et al. (Frontiers in Microbiology, 2017)
Inflammation is one of the hallmarks of prostate cancer. The origin of inflammation is unknown, but microbial infections are suspected to play a role. In previous studies, the Gram-positive, low virulent bacterium Cutibacterium (formerly Propionibacterium) acnes was frequently isolated from prostatic tissue. It is unclear if the presence of the bacterium represents a true infection or a contamination. Here we investigated C. acnes type II, also called subspecies defendens, which is the most prevalent type among prostatic C. acnes isolates. Genome sequencing of type II isolates identified large plasmids in several genomes. The plasmids are highly similar to previously identified linear plasmids of type I C. acnes strains associated with acne vulgaris. A PCR-based analysis revealed that 28.4% (21 out of 74) of all type II strains isolated from cancerous prostates carry a plasmid. The plasmid shows signatures for conjugative transfer. In addition, it contains a gene locus for tight adherence (tad) that is predicted to encode adhesive Flp (fimbrial low-molecular weight protein) pili. In subsequent experiments a tad locus-encoded putative pilin subunit was identified in the surface-exposed protein fraction of plasmid-positive C. acnes type II strains by mass spectrometry, indicating that the tad locus is functional. Additional plasmid-encoded proteins were detected in the secreted protein fraction, including two signal peptide-harboring proteins; the corresponding genes are specific for type II C. acnes, thus lacking from plasmid-positive type I C. acnes strains. Further support for the presence of Flp pili in C. acnes type II was provided by electron microscopy, revealing cell appendages in tad locus-positive strains. Our study provides new insight in the most prevalent prostatic subspecies of C. acnes, sp. defendens, and indicates the existence of Flp pili in plasmid-positive strains. Such pili may support colonization and persistent infection of human prostates by C. acnes.